Pengembangan Perangkat Pembelajaran Membaca Permulaan Berbasis Metode Steinberg Yang Efektif di Sekolah Dasar - Kasmawati Kasmawati; La Sisi; Arna Juwairiyah; Chairan Zibar L. Parisu (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
The purpose of this research is to find out, explain, explain, and develop learning tools used in the process of beginning reading based on the Steinberg method which is effective in elementary schools. The development of early reading learning tools in this study refers to the 4-D Thiagarajan Model. This model consists of four stages of development, namely define, design, develop, and desseminate or be adapted into a 4-P model, namely defining, designing, developing, and distributing modified steps in the define stage. The research subject is the initial reading learning device in the form of a syllabus, lesson plans and teaching materials to be developed. Research data in the form of qualitative data. Data collection techniques using observation, and interviews. The data analysis technique uses qualitative analysis. The results showed that all 28 students consisting of 10 males, 18 females, who took part in learning using the Steinberg method-based early reading learning tools increased their ability to begin reading with a percentage between 10-88 percent. The average initial reading ability at the pretest reached 51.4% while at the posttest it reached 71.3%. The conclusion of this study is that all students who take part in learning using the Steinberg method of early reading learning tools increase their ability to read beginnings. The development of early reading learning tools based on the Steinberg method is needed to improve the quality of the early reading learning process in grade I.